Lactic Acid Bacteria Isolated from the Gastro-Intestinal Tract of Chicken: Potential Use as Probiotic - Harimurti, S; Nasroedin, ES; Nasroedin, Nasroedin; Kurniasih, Kurniasih (Universitas Jenderal Soedirman, Faculty of Animal Science, Purwokerto-Indonesia, 2007)
Lactic acid bacteria have been suggested to have several beneficial effects on human and animals. These bacteria, indigenous to the gastro-intestinal tract, are important in regulating the balance among the desirable and undesirable intestinal microflora and in controlling enteric pathogenic infection in the host. Objectives of this research are to obtain lactic acid bacteria isolates from gastro-intestinal tract of chicken and to screen their ability as a probiotic agent i.e., their antagonistic against pathogenic bacteria, their survival at low pH and high concentration of bile salt. In this research, 74 samples used as sources of bacteria, and among them only 11 samples could be isolated as lactic acid bacteria with the total number of isolates of 61. Based on the preliminary screening i.e., their antagonistic factor against pathogenic bacteria, 20 isolates was further studied. Based on the identification scheme, these isolates belong to three species, i.e., Lactobacillus murinus, Pediococcus acidilactici, and Streptococcus thermophilus. The result showed that most isolates grow well in the media with the initial pH of 5.5, but their growth were retarded when the initial pH 3.5. Only one isolate Streptococcus thermophilus Kp-2 showed its growth at initial pH of 3.5. All isolates did not show any growth at initial pH 2.5, though their viability still high. The result based on the isolates resistance to bile salt showed that most isolates could grow at media with 0.20% of bile salt. Their growth was inhibited with the increasing bile salt concentration. However, few isolates could grow well at media with 1% of bile salt. Based on their characteristics three isolates i.e., Lactobacillus murinus Ar-3, Streptococcus thermophilus Kp-2, and Pediococcus acidilactici Kd-6 were selected as probiotic agents for the continuing research. i.e. production of biomass and its application to chicken production. (Animal Production 9(2): 82-91 (2007) Key Words : Lactic acid bacteria, gastro- intestinal tract of chicken, probiotic agents